The Relationship between Family Social Support and Self-Efficacy in Career Decision-Making of Final Year University Students - Adinda Salwani; Wening Cahyawulan (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2022)
The purpose of this research is to determine the relationship between family social support and self-efficacy in career decision-making self-efficacy of final-year students. This is quantitative research with correlational design. The convenience sampling technique used to obtain a sample size of 402 final-year university students. Data were collected using a questionnaire consist of biographical related question and Family Support Measure instrument consisting of Family of Origin Career Development Support, Parent Intentional Career-Related Interactions, and Career Decision Self-Efficacy-Short Form (CDSE-SF). The validity and reliability test shows that all items were valid and reliable with reliability tests of 0.870, 0.911, and 0.973 for the Family of Origin Career Development Support, Parent Intentional Career-Related Interactions, and CDSE-SF. The results showed a significant positive relationship between family social support and self-efficacy in career decision-making of final-year students. Therefore, it is expected that the higher education career service center can use family factor as a source of support in the career service process.